The meat market: a dea international perspective and an econometric behavioral model for Brazil - Geraldo da Silva e Souza; Eliane Gonçalves Gomes; Dirceu João Duarte Talamini; Renner Marra (Production)
We describe the relative participation of the Brazilian meat market (beef, pork and chicken) in total agribusiness exports and in total country exports. An analysis of the world meat market is carried out from the point of view of the values of consumption, production, exports and imports. A DEA (data envelopment analysis) approach is then used to generate classifications of the importance of countries in the meat world market, and the insertion of Brazil into this market is viewed from these perspectives. A partial equilibrium model for the meat market is fitted to Brazilian data by a three-stage least squares procedure. The model is consistent with the data and is used for simulation purposes. In this context, we investigate the joint and separate effects of changes in the corn price and in the exchange rate on the market of endogenous variables, ceteris paribus.